Research on application of dynamic threshold least squares Beidou positioning algorithm in Beidou geological disaster monitoring in Three Gorges Reservoir Area. Issue 12 (9th June 2020) - Lei, Guoping; Luo, Xiuying; Liu, Zhiyuan; Xiao, Ke; Dai, Minlu
Abstract: At present, China's Beidou Navigation Satellite System (BDS) has been successfully applied in all walks of life and entered a period of rapid development. The least squares algorithm is often used to solve problems in the application of BDS, while the quaternary nonlinear equation set is used for solving the BDS PVT positioning and timing issues. The solution of least squares is an iterative process, but if the convergence threshold is too small in the iterative process, it may lead to continuous iteration without convergence. Therefore, a least squares algorithm based on dynamic threshold was proposed in this paper. The proposed algorithm could continue iteration until convergence by increasing the system's dynamic threshold. At the same time, the proposed algorithm could also change the satellite combination in time, so as to conduct the positioning and calculation again over the threshold value that increases to a fixed value but fails to converge. Also, the BDS computation process was programmed and simulated. Simulation results show that even if the threshold is set too small, it converges well. During the operation of Beidou‐based geological disaster monitoring system in the Three Gorges Reservoir Region, the algorithm not only effectively prevents the program failure in Beidou satellite positioning caused by the convergence failure of algorithm iteration but also greatly improves the stability and reliability of the system program operation. Abstract : A least square Beidou positioning algorithm based on dynamic threshold is proposed. The proposed algorithm could continue iteration until convergence by increasing the system's dynamic threshold. At the same time, the proposed algorithm could also change the satellite combination in time, so as to conduct the positioning and calculation again over the threshold value that increases to a fixed value but fails to converge.